Limitierte Kunstreihen 1968-1983. - Rosenthal, Philip; Honisch, Dieter; Fischer-Treyden, Elsa (Selb : Rosenthal AG, 1983)
Grieshaber, HAP ; Piene, Otto ; Wunderlich, Paul ; Moore, Henry ; Fontana, Lucio ; Kokoschka, Oskar ; Paolozzi, Eduardo ; Dali, Salvador ; Uecker, Günther ; Vasarely, Victor ; Hajek, O.H. ; Hundertwasser, F. ; Mavignier, Almir ; Wesselmann, Tom ; Fuchs, Ernst ; etc.
Duits
boek